PENGARUH KARAKTERISTIK KOMITE AUDIT DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - Dwikusumowati, Meriam Zalzabilani; Nur Rahardjo, Shiddiq (Diponegoro Journal of Accounting, 2013)
This study was aimed to analyse the influence of audit committee characteristics and firm characteristics on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2009-2011. The independent variables were audit committee characteristics (independency, financial expertise, size, and activity of audit committee) and firm characteristics (leverage, firm size, and profitability), while the dependent variable was earnings management wihich was measured by discretionary accruals using the Modified Jones Model. The hypothesis proposed in this study was that audit committee and firm characteristics influenced earnings management.Data of this study were obtained from the annual report and financial statements of manufacturing firms drawn from the Indonesia Stock Exchange. The population of this study were manufacturing companies listed on the Indonesia Stock Exchange during the years 2009-2011. The samples were determinated by purposive sampling method, and 140 companies were then collected. The hypothesis was tested using multiple regression analysis. The results of this study showed that financial expertise of audit committee and profitability had significant influence on earnings management. On the other hand, independency, size, and activity of audit committee, leverage, and firm size had no significant influence on the earnings management.